Optimization of bifurcating channel cooling system for double inclined conductive panel system under inclined magnetic field - Selimefendigil, Fatih; El-Sinawi, Abdulaziz Hussein; Öztop, Hakan Fehmi (Elsevier France-Editions Scientifiques Medicales Elsevier, 2023)
A novel cooling system with wavy branching channels is proposed considering nano-enhanced magnetic field effects for thermal management of double inclined conductive panels. Thermal performance assessment is conducted by varying Reynolds number (250 <= Re <= 1000), Hartmann number (0 <= Ha <= 400), magnetic field inclination (250 <= r <= 1000), amplitude (0 <= Af <= 0.4) and wave number (1 <= N f <= 12). As the cooling fluid, water with Ag-MgO hybrid nanoparticles is considered. Temperature drops of 4.5 degrees C and 2.6 degrees C are obtained with the highest Re for left inclined panel (p1) and right inclined panel (p2). As the vortex distribution is highly affected for the wavy branching channels by the magnetic field strength, its impact on the cooling performance for p1 and p2 are different. It shows a favorable impact for panel p2 while average Nusselt number (Nu) increments become 10% and 6.3% when using flat and wavy branching channels at the highest magnetic field strength. For panel p1, varying inclination of magnetic field results in average surface temperature drop of 1.6 degrees C for wavy channel. The optimum value of wave number in the corrugated branching channel is Nf=2 for achieving the highest cooling performance while higher amplitudes of corrugation has favorable impacts on the cooling for each of the panels. As compared to un-cooled panel configuration, utilization of flat branching channel with nano-enhanced magnetic field results in 47.4 degrees C and 48.9 degrees C surface temperature drops for panels p1 and p2. Optimization based on COBYLA is utilized to achieve additional temperature drops as compared to parametric computational fluid dynamics. The optimum values of (Ha, r, Af) are obtained as (40, 89, 0.04) at Re=100 and (40, 60.8, 0.0038) at Re=1000. The proposed single cooling method with wavy branching channel under nano-enhanced magnetic field can be used and further developed for effectively cooling of photo-voltaics with inclined arrangement, electronic cooling and many other heat transfer devices.
Keywords: Bifurcating channel; Magnetic field; Nanofluid; Wavy surface; Finite element method; Optimization